Ecological and health impacts of tobacco farming in Pakistan: A mixed-methods approach toward a sustainable pathway for agricultural transition - Abdul Rasool Khoso; Gu Jintu; Qingjun Chen; Muhammad Javed Sheikh; Wang Suyuhan; Shahnaz Bhutto (Tobacco Induced Diseases)
Introduction Tobacco farming plays a crucial role in the livelihoods of many rural communities in Pakistan, particularly in Khyber Pakhtunkhwa (KPK). However, this agricultural practice is associated with severe environmental degradation and significant health risks to workers during cropping.